The missionary self-perception of Pentecostal/Charismatic church leaders from the global South in Europe : bringing back the Gospel - Währisch-Oblau, Claudia. (Global Pentecostal and Charismatic Studies, 2009)
In a situation of growing interest in the religion of migrants, there are still few publications dealing with pentecostal and charismatic Christians from the global South and the churches they have been starting all over Europe. This ground-breaking study, based on extensive interviews conducted during a nine-year research period encompassing more than 100 churches, describes how pentecostal /charismatic migrant pastors live out their pastoral role, how they construct their missionary biographies, and how they conceptualize and practice evangelism. The result is a comprehensive portrait of an immigrant group which does not define itself as victimized and in need of assistance, but as expatriate agents with a clear calling and a vision to change the continent they now live inches.